The effectiveness of Kinesio Taping in improving pain and edema during early rehabilitation after Anterior Cruciate Ligament Reconstruction: A Prospective, Randomized, Control Study - Labianca, Luca; Andreozzi, Valerio; Princi, Giorgio; Princi, Alessandro A.; Calderaro, Cosma; Guzzini, Matteo; Ferretti, Andrea (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: The Kinesio Taping (KT) is being increasingly applied in physical therapy and rehabilitation. The aim of this study was to evaluate the effect of KT on an early rehabilitation program, in combination with the standard protocol after ACL reconstruction (ACLR). Methods: This study enrolled 52 male patients, aged 18 to 45 years, who underwent ACLR with doubled gracilis and semitendinosus tendon (DGST) autograft. The patients were randomized into 2 groups: Group A (the control group) which received a standard rehabilitation protocol, and Group B (the experimental group), which had the same rehabilitation protocol plus the KT application. Pain intensity, range of motion, edema, thigh circumference, Tegner-Lysholm Scale and KOOS scale were measured at the second and fourth week follow-ups. Results: Patients in the experimental group showed significant results during the second week for both pain and edema reduction compared to the control group (p< 0.05). After 4 weeks of rehabilitation, pain intensity in the two groups was similar (n.s.), while edema reduction in the experimental group showed a significant result compared to the control group (p< 0.05). Nevertheless, the other outcomes did not show significant differences. Conclusions: The application of KT after ACLR contributed to relieve pain and reduce edema in the early postoperative rehabilitation period. Other potential benefits of KT on muscle activation and strength should be investigated through a longer follow-up and a targeted test.